Jak Inhibitors for Treatment of Autoimmune Diseases: Lessons from Systemic Sclerosis and Systemic Lupus Erythematosus - Przemysław Kotyla; Olga Gumkowska-Sroka; Bartosz Wnuk; Kacper Kotyla (MDPI AG, 2022)
Systemic sclerosis and systemic lupus erythematosus represent two distinct autoimmune diseases belonging to the group of connective tissue disorders. Despite the great progress in the basic science, this progress has not been translated to the development of novel therapeutic approaches that can radically change the face of these diseases. The discovery of JAK kinases, which are tyrosine kinases coupled with cytokine receptors, may open a new chapter in the treatment of so far untreatable diseases. Small synthetic compounds that can block Janus kinases and interact directly with cytokine signalling may provide therapeutic potential in these diseases. In this review, we discuss the therapeutic potential of Jak kinases in light of the cytokine network that JAK kinases are able to interact with. We also provide the theoretical background for the rationale of blocking cytokines with specific JAK inhibitors.